Engineering probiotic Escherichia coli for inflammation-responsive indoleacetic acid production using RiboJ-enhanced genetic circuits - Seung-Gyun Woo; Seong Keun Kim; Seung-Goo Lee; Dae-Hee Lee (Journal of Biological Engineering)
Abstract Background As our understanding of gut microbiota’s metabolic impacts on health grows, the interest in engineered probiotics has intensified. This study aimed to engineer the probiotic Escherichia coli Nissle 1917 (EcN) to produce indoleacetic acid (IAA) in response to gut inflammatory biomarkers thiosulfate and nitrate. Results Genetic circuits were developed to initiate IAA synthesis upon detecting inflammatory signals, optimizing a heterologous IAA biosynthetic pathway, and incorporating a RiboJ insulator to enhance IAA production. The engineered EcN strains demonstrated increased IAA production in the presence of thiosulfate and nitrate. An IAA-responsive genetic circuit using the IacR transcription factor from Pseudomonas putida 1290 was also developed for real-time IAA monitoring. Conclusions Given IAA’s role in reducing gastrointestinal inflammation, further refinement of this strain could lead to effective, in situ IAA-based therapies. This proof-of-concept advances the field of live biotherapeutic products and offers a promising approach for targeted therapy in inflammatory bowel diseases.